The KMT1A-GATA3-STAT3 Circuit Is a Novel Self-Renewal Signaling of Human Bladder Cancer Stem Cells - Zhao Yang; Luyun He; Kaisu Lin; Yun Zhang; Aihua Deng; Yong Liang; Chong Li; Tingyi Wen (2017)
Abstract Purpose: Bladder cancer is one of the most common urinary malignancies worldwide characterized by a high rate of recurrence and no targeted therapy method. Bladder cancer stem cells (BCSCs) play a crucial role in tumor initiation, metastasis, and drug resistance. However, the regulatory signaling and self-renewal mechanisms of BCSCs remain largely unknown. Here, we identified a novel signal, the KMT1A-GATA3-STAT3 circuit, which promoted the self-renewal and tumorigenicity of human BCSCs. Experimental Design: In a discovery step, human BCSCs and bladder cancer non-stem cells (BCNSCs) isolated from primary bladder cancer samples #1 and #2, and the bladder cancer cell line EJ were analyzed by transcriptome microarray. In a validation step, 10 paired bladder cancer and normal tissues, different tumor cell lines, the public microarray datasets of human bladder cancer, and The Cancer Genome Atlas database were applied for the verification of gene expression. Results: KMT1A was highly expressed and responsible for the increase of tri-methylating lysine 9 of histone H3 (H3K9me3) modification in BCSCs compared with either BCNSCs or normal bladder tissue. GATA3 bound to the -1710∼-1530 region of STAT3 promoter and repressed its transcription. H3K9me3 modification on the -1351∼-1172bp region of the GATA3 promoter mediated by KMT1A repressed the transcription of GATA3 and upregulated the expression of STAT3. In addition, the activated STAT3 triggered self-renewal of BCSCs. Furthermore, depletion of KMT1A or STAT3 abrogated the formation of BCSC tumorspheres and xenograft tumors. Conclusions: KMT1A positively regulated the self-renewal and tumorigenicity of human BCSCs via KMT1A-GATA3-STAT3 circuit, in which KMT1A could be a promising target for bladder cancer therapy. Clin Cancer Res; 23(21); 6673–85. ©2017 AACR.